1997
DOI: 10.2113/gsjfr.27.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Amphistegina gibbosa populations in the Florida Keys (U.S.A.) to a multi-year stress event (1991-1996)

Abstract: Calcifying organisms with endosymbiotic algae produce a major portion of the calcium carbonate sediments in tropical oceans. In 1982-1983, global coral bleaching events revealed the emergence of serious breakdowns in these important symbiotic associations. In 1991-1992, similar problems appeared in Amphistegina spp., the most abundant reef dwelling algal symbiont-bearing foraminifer worldwide.Since summer 1992, A. gibbosa populations from Conch Reef in the Florida Keys (USA) have been monitored for visible evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…In addition, we documented that bleaching visible in reflected light typically began in individuals ∼ 0.6 mm in diam. and increased as the foraminifers grew (Williams et al 1997). The second enigma was “How could these protists continue to grow at the same time their cytoplasm was deteriorating?” The answer may be in the ectoplasm, which appears to function somewhat independently of the endoplasm (see also Travis and Bowser 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we documented that bleaching visible in reflected light typically began in individuals ∼ 0.6 mm in diam. and increased as the foraminifers grew (Williams et al 1997). The second enigma was “How could these protists continue to grow at the same time their cytoplasm was deteriorating?” The answer may be in the ectoplasm, which appears to function somewhat independently of the endoplasm (see also Travis and Bowser 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Because these protists are mobile and exhibit phototaxic behavior (Lee, McEnery, and Garrison 1980; Zimiri et al 1974), the dose of radiant energy they actually experience in their microhabitat is unknown. However, our experimental results strengthen previous field and laboratory evidence (Hallock et al 1995; Talge et al 1997; Williams et al 1997) implicating photic stress rather than thermal stress in bleaching of A. gibbosa in the Florida Keys in the 1990s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, smaller size and faster turnover will allow foraminiferal assemblages to recover and reach successional endpoints more rapidly. Although ecological studies on foraminiferal succession in the Pacific Region are lacking, ecological studies of symbiont-bearing foraminifera in the Florida reef tract have shown that populations recover from bleachingrelated mortality events or hurricane scouring in a matter of months to at most a year or two (Williams et al 1997;Hallock et al 2006, Baker et al 2009). This is in contrast with coral communities which may need decades to fully recover colony density and diversity (Done et al 2007;Wakeford et al 2008).…”
Section: Coralsmentioning
confidence: 99%
“…Bleaching in foraminifers was first described in laboratory experiments (Hallock et al, 1986), however, it was unknown in field populations until Hallock et al (1993) collected several specimens of Amphistegina gibbosa that appeared "spotted" during a post-bleaching coral survey in 1988. Since 1991, some bleaching of A. gibbosa has been consistently observed in field samples from the Florida Keys during summer months (Hallock et al, 1995;Williams et al, 1997;Mendez-Ferrer et al, 2018). Symbiont loss may affect over 80% of the total adult Amphistegina population; individual specimens display unusual color sometimes restricted to a few white spots, or progressing to near absence of symbiont color (Hallock et al, 1995;Mendez-Ferrer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%